Estrous Synchronization in Peranakan Etawah Goat Using CIDR-G - Semiadi, G; Sutama, I Ketut; Syaefudin, Y (ANIMAL PRODUCTION, 2003)
A study on the effectiveness on estrous synchronization using CIDR-G in peranakan etawah (PE) goat was conducted. Twenty-eight multiporous PE goats were randomly allocated to two groups (A & B) and CIDR was inserted for 16 days. In group A CIDR was replaced at day eight and in group B CIDR was stayed intake until day 16. Estrous sign was detected using castrated teaser 20 hours post CIDR withdrawal and evaluated every four hours until the estrous sign was disappeared. At the same time of estrous detection, blood sample for progesterone assay, from five selected goats in each group was collected into heparins vacuum blood tube, collected via jugulars vein. From this study it was shown no significant differences in initial time of estrous sign between the groups (38.33 vs. 33.22 hours post CIDR withdrawal). Similarly there was no significant difference in the length of estrous between the groups (54.22 vs. 48.65 hours). The lowest mean progesterone hormone concentration (<0.50 ng/ml) occurred 78 hours post CIDR withdrawal. From this study it was concluded that using CIDR-G in PE goat is effective and no replacement is needed between the synchronization periods. (Animal Production 5(2): 83-86 (2003)Â Key Words : Etawah Goat, Synchronization, Estrous, CIDR